Harvesting mouse suprachiasmatic nucleus by vibrating microtome for diurnal transcriptome analysis - Akanksha Bafna; Petrina Lau; Gareth Banks; Patrick M. Nolan (STAR Protocols, 2023)
Summary: The mammalian suprachiasmatic nucleus (SCN) is the principal circadian clock that synchronizes daily behavioral and physiological responses in response to environmental cues. Here, we present a protocol for harvesting mouse SCN by vibrating microtome for diurnal transcriptome analysis. We describe steps for mouse entrainment, isolation of the SCN, tissue preparation, slicing with a vibratome, and handling of the harvested SCN for RNA extraction. This protocol can also be used for harvesting other mammalian brain regions for genomic studies. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.